Transition, integration and convergence - The case of Romania - - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2010)
This volume comprises several studies and papers published in the last decades. They have been selected and ranged so that to provide a minimum of coherence concerning the phases which Romania has crossed in her way to the advanced socio-economic system of European type: transition to the market economy, accession to the EU, the economic convergence in the three fundamental domains: institutions, real economy, and nominal economy. The readers may find in this volume a description of debates, difficulties and solutions adopted for building-up the market economy by a state being in a profound transformation from weak transition institutions towards hard democratic institutions. Because the transition to the market economy and the association of Romania with the EU and then the integration presenting strategic political decisions, I have included in this work two studies devoted to the political forces state and political parties that elaborated and applied these strategic decisions underlining their structure, role and function and their transformation. Integration into the EU of a country like Romania, which emerged from a different system comparing with the West-European one, has proved to be difficult and lasting many years because of the structural transformations. In five chapters I am referring to the essential characteristics of the integration process, such as: market liberalization, competitiveness of the local (national) firms on the national and EU markets, institutional reforms so that the institutions of candidate countries have to become compatible with those of the EU and finally the perspective assessment to find out the real and nominal convergence. Putting into practice the EU competitivity and cohesion principles, Romania has good prospects to close, in a reasonable time, the economic gap and to be admitted into the Euro Zone. Although the real convergence of Romania with the EU requires higher growth rates for the former, a new approach is compulsory to take into consideration the environment quality, the natural resources and the equity between the present and the future generations as natural resource consumers. Just these problems have determined me to include in this volume the last two chapters which, on the one hand, try to prove the necessity of the economy growth harmonization with the environment evolution as well as the saving of the energy resources, and, on the other hand, to point out the main ways to be followed and instruments to be used.
Keywords: C21; E02; E22; F36; F55; F59; O41; O43; O47; 330; transition; integration; convergence; cohesion; formal institutions; informal institutions; transaction cost; acquis; compliance; institutional capital; regression